A Study on the Relationship Between Organizational Culture and Service Quality at Great Eastern Life Assurance (M) Berhad - Felly Dalilina, Nurulhuda (2011)
Much attention has been focused on how to enhance service quality in order to meet customer expectations and demand. However, relatively limited studies focus on the relationship between organizational culture and service quality in insurance industry in Malaysia. The purpose of this study is to examine the relationship between organizational culture and service quality. Data were collected from 120 Customer Service employees in Great Eastern Life Assurance (M) Bhd and gathered through questionnaire. The result was being analyzed by using Statistical Package for Social Science (SPSS)version 19.Based on the data analysis,independent variables such as involvement,adaptability,strategic direction,and empowerment have positive correlations with service assurance,service reliability,and service equipment. Recommendations and implications for future research and practices were also discussed.